The collaborative interactions of preschool children in solving problems in a collaborative virtual environment - Paniagua-Esquivel, Cristina (2020)
Background: When trying to understand others, it requires a series of complex skills. Meaning able to comprehend what one’s intentions or actions are and then responding accordingly. As a result, these skills begin to develop at around the age of four and are key to peer interaction. The objective of the study was to analyze the interaction of preschool children had among each other, when they play in a virtual collaborative environment. Method: The participants were seven triads (21 students) of the transition level (11 children, M = 6 years, 3 months, SD = 0.38) and a videogame designed for the participants to play in dyads, coordinating and negotiating to move forward. Results:  Within the main results, it stood out that there is an association between verbalizations and changes in gestures. This allows children to solve problems collaboratively. Although it is not a study of evolutionary development, it is a contribution to understanding a skill that implies a level of cognitive development: thus, understanding when is the time when children can begin to collaborate. Conclusions: When observing interactions, it can seem difficult to achieve a common goal. Yet the results of the study show that the children are capable of understanding not only their own perspective but also of others. As a result, this allows them to resolve collaborative tasks, similar to the one presented in the study.